Short-term temporal variability of surface wind speed over Central Spitsbergen, Svalbard - Láska, K.; Chládová, Z. (Zuzana); Hošek, J. (Jiří) (2017)
Atmospheric boundary-layer processes as well as the wind field on the Svalbard archipelago differ significantly due to the local forcing effects related\nto complex topography, land-surface characteristics or sea ice occurrence. In contrast to intense atmospheric research carried out in the vicinity of the\nlargest settlements and research stations, information about the wind field structure from the other part of the Svalbard is still insufficient. Therefore,\nthe aim of the study is to use yearlong measurement in central Spitsbergen to 1) analyse the temporal variation in the near-surface wind field and 2)\nevaluate the relationship between large-scale weather systems and the wind speed among different locations within the fjord.\nWe focused primarily on the analysis of the near-surface wind characteristics measured in Petuniabukta and Mimerbukta close to Russian settlement\nPyramiden (Fig. 1) during 2013. Two automatic weather stations were located on the raised marine terrace at altitudes from 15 and 20 m a. s. l.\nPattern of atmospheric circulation was identified using 850 hPa geopotential heights and geostrophic winds. Moreover, Weather Research and\nForecasting (WRF) mesoscale model outputs (Skamarock et al. (2008) with the Quasi-Normal Scale Elimination parameterization scheme with 1-km\nhorizontal resolution of the inner domain were used for identification of local circulation systems. We found that the large-scale flows were often\nmodified by channelling and drainage effects accompanied by an increase on local wind speed in the coastal zone. Moreover, the occurrence of low\nlevel jets were identified and successfully simulated by the WRF model.